The effect of orientation and mobility curriculum on the academic achievement of visually impaired children among public and private institutions of Lahore - Malik, Shazia; Abdul Manaf, Umi Kalthom (Human Resource Management Academic Research Society, 2018)
The present study endeavors to assess the impact of orientation and mobility curriculum associated with special education for visually impaired students in Pakistan. This study aims to scrutinize whether the present special education curriculum for visually impaired children would be considered effective without the involvement of orientation and mobility curriculum or not. A questionnaire consisting of 10 items was developed for data collection. The sample of the study consisted of 110 visually impaired students among public and private visually impaired institutes in Lahore, Pakistan, according to the table of (Kerjice & Morgan, 1970). Among the participants, 67 were boys and 43 were girls, age ranged from 5 to 20 years, and they were from starters to 6th grade levels. The present study approves that the visually impaired students can be promoted from the certain nurturing situation, when they have least educational or psychological hindrances. The study indicates that the visually impaired students can actively perform their essential part in presenting excellent educational achievement based on orientation and mobility curriculum for the visually impaired children., However, some hazards incidents have depressed the whole contribution of this relegated class of students from their basic opportunity of Education.